2016
DOI: 10.5194/esd-2016-37
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network-based detection scheme of the jet stream core

Abstract: The comment was uploaded in the form of a supplement: http://www.earth-syst-dynam-discuss.net/esd-2016-37/esd-2016-37-AC4-supplement.pdf Interactive comment on Earth Syst. Dynam. Discuss.,

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…In terms of the mean flow, there is a significant weakening of the westerlies in most parts of the study region and a poleward shift and narrowing of the PJ axis over eastern North America and the North Atlantic. This agrees with the outcome from other work (Wilcox et al, 2012;Molnos et al, 2017). The same is true for the meridional position of the subtropical jet stream over North Africa, indicating that the Tropics are extending poleward, as suggested by Wang (2001), Kossin (2014) and Lucas et al (2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of the mean flow, there is a significant weakening of the westerlies in most parts of the study region and a poleward shift and narrowing of the PJ axis over eastern North America and the North Atlantic. This agrees with the outcome from other work (Wilcox et al, 2012;Molnos et al, 2017). The same is true for the meridional position of the subtropical jet stream over North Africa, indicating that the Tropics are extending poleward, as suggested by Wang (2001), Kossin (2014) and Lucas et al (2014).…”
Section: Discussionsupporting
confidence: 92%
“…This is indicative of a general poleward shift of tropical and extratropical circulation zones and has also been reported for the Southern Hemisphere (e.g. Wilcox et al ., ; Molnos et al ., ). It means that over the last 40 years the typical winter situation is getting closer to the former summer situation with the PJ trapped in a more poleward and spatially confined position (see subsection 3.1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Büntgen et al (2018) reported elevated 14 C values for some trees growing above 60ºN at the peak of the AD 774/5 Miyake event (Miyake et al 2012). The position of the present-day polar jet stream, which delineates the polar front, is presented as a latitudinal probability distribution by Molnos et al (2017), but a simple boundary is not easily established. We therefore used 60ºN for comparison of northerly trees with the other data.…”
Section: Intcal20 14 C Calibration Curve 729mentioning
confidence: 99%
“…Jet streams are upper-level fast currents of westerly winds that circulate around the hemisphere. Under climate change a 20 weakening of the northern subtropical jet stream in winter is observed by most studies (Molnos et al, 2017;Rikus, 2015) though a few studies observe also a positive trend (Pena-Ortiz et al, 2013). The underlying drivers for those changes are still debated.…”
mentioning
confidence: 99%